Teachers' Pedagogical Skills to Instill Islamic and Muhammadiyah Values to Face the Era of Society 5.0: Kecakapan Pedagogis Guru untuk Menanamkan Nilai-nilai Islam dan Kemuhammadiyahan Menghadapi Era Society 5.0 - Achmad, Abdul Kholid (Universitas Muhammadiyah Sidoarjo, 2024)
Education is a vital component of society, serving as a primary benchmark for growth and development, particularly in the Society 5.0 era, which Manuel Castell describes as the information age. This society focuses on information and transactions within both physical and virtual spaces. In the context of Society 5.0, education leverages big data to enhance abilities and open opportunities across various life domains, addressing social challenges. The relationship between education and societal change is profound, as education within the Muhammadiyah Association aims to prepare individuals to grow as people aware of the presence of Allah SWT and mastering knowledge, technology, and the arts. Education also aims to develop students' potential to become people of faith, piety, noble character, knowledge, competence, creativity, independence, and responsible citizenship. Faced with the rapid and intelligent societal changes, educational institutions must prepare students to be competitive. Teachers, as key elements in education, must continually improve their capacities while adhering to religious, cultural, and national values. Teachers' roles, with their intuition and hearts, are crucial in deeply internalizing values through their daily exemplary behavior.